(untitled) (KULT_online, 2020)
Post-truth has recently garnered a lot of attention, yet its definition escapes us. Steve Fuller challenges the a priori contempt for post-truth most scholarship seems to have. Instead, he sees post-truth as a stage in the progressive democratization of knowledge. He questions the anti-intellectual label it often bears and claims that its negative consequences are but “growth pains of a maturing democratic intelligence” (181). The book provides compelling analyses of the post-truth condition across a breadth of disciplines and fills in countless lacunae in the study of post-truth.